Maternal immunization promotes the immune response of neonates towards hepatitis B vaccine. Issue 12 (18th April 2013) - Zhang, W.; Guo, Z.; Zhang, L.; Liu, Z.; Li, J.; Ji, Z.; Xu, R.; Zhao, N.; Li, F.; Chen, X.; Yan, Y.; Zhang, J.; et al.
Summary: Infants infected with hepatitis B virus (HBV) face the risk of developing severe complications. Unfortunately, in spite of universal vaccination programmes, 5% or more of vaccinated newborns still do not achieve protective levels of anti‐hepatitis B virus surface antigen titres (anti‐HBs). The aim of this study was to use animal experiments and population‐based research to determine whether maternal vaccination against HBV affects the outcome of neonatal vaccination. Six sows and 53 newborn piglets were used for this study and randomly assigned to the vaccination group (three 20 μg doses of recombinant HBV vaccine). All the piglets were followed up to 10 weeks of age, and peripheral blood was withdrawn for measurement of anti‐HBs. A cross‐sectional study was also conducted on 449 mothers with infants. A structured questionnaire was used to collect demographic, medical and maternal data, and their peripheral blood was collected for measurement of anti‐HBs. The results of animal experiments demonstrated that nonvaccinated piglets born to vaccinated sows and nonvaccinated piglets born to nonvaccinated sows were negative for anti‐HBs. Repeated measures analysis of variance showed that the titres of anti‐HBs in vaccinated piglets born to vaccinated sows were significantly higher than in vaccinated piglets born to nonvaccinated sows ( P  < 0.05). In a population‐based study, a cumulative logistic regression analysis showed that the strongest influences on neonatal anti‐HBs titres were delay of the first vaccination dose [OR = 3.02(95% CI: 1.72–5.30)] and maternal anti‐HBs titres [OR = 2.48(95% CI: 2.03–3.04)]. In conclusion, high maternal anti‐HBs titres can enhance the response to HBV vaccination in infants.